Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Setting $S^{n} := \{x\in\mathbb{R}^{n+1}: \|x\| = 1\}$, and labelling the north and south poles as $N:= (0,\ldots,0,1)$, $S:=(0,\ldots,0,-1)$, I can set the coordinate charts up as follows:

Let $U_N = S^n - N$ and $U_S = S^n - S$.

Taking the usual stereographical projections $\phi_{N}:U_{N}\to\mathbb{R}^{n}$ and $\phi_S : U_S \to\mathbb{R}^n$, we turn $S^n$ into a topological manifold of dimension $n$.\ \ I'm having trouble verifying that this structure satisfies the definition of a differentiable manifold, as I do not know how to check that $f:=\phi_{N}\circ \phi_{S}^{-1}:\mathbb{R}^{n} - 0$ is $C^{\infty}$. It is clear how to show (once I draw the picture) that $f$ is a bijection.

Do I need to derive a formula for the $\phi_{N}$ and $\phi_{S}^{-1}$ map in order to show that it is $C^{\infty}$? Any references I found this in usually display it as an example and mention casually that it is easy to show that $f$ is $C^\infty$, but I'm not even sure how to begin.

share|improve this question
1  
Yes, just write down a formula for the composition and then verify that it is infinitely differentiable. Once you have a formula for the $\phi$ you should be able to write down a formula for the composition; this involves knowing what stereographic projection is. –  Jason Polak Oct 28 '12 at 0:41

1 Answer 1

up vote 1 down vote accepted

Let $y = \phi_N (x)$, then this is equivalent to $N+t(x-N) = (y,-1)$, with slight abuse of notation. Since $1+t(x_{n+1}-1) = -1$, it follows that $y = \frac{2}{1-x_{n+1}} (x_1,...,x_n)$. Hence $\phi_N$ is smooth on $\mathbb{R}^{n+1} \setminus \{N\} \supset U_N$ (ie, smooth as a mapping $\mathbb{R}^{n+1} \setminus \{N\} \to \mathbb{R}^n$).

Now suppose $x = \phi_N^{-1}(y)$, again equivalent to $N+t(x-N) = (y,-1)$. We wish to find the $x \in \partial B(0,1)$ that satisfies this equation. Rearranging this equation gives $t x = (y, t-2)$ (again a slight abuse of notation). Summing the squares of the components gives $t^2 \sum_{i=1}^{n+1} x_i^2 = \sum_{i=1}^{n} y_i^2+(t-2)^2 = \sum_{i=1}^{n} y_i^2 + t^2 -4t +4$. If $x \in \partial B(0,1)$, this gives $t = 1 + \frac{1}{4}\sum_{i=1}^{n} y_i^2$, from which it follows that $\phi_N^{-1}(y) = \frac{1}{1 + \frac{1}{4}\sum_{i=1}^{n} y_i^2} (y, -1+\frac{1}{4}\sum_{i=1}^{n} y_i^2)$.

It is easy to see that $\phi_N^{-1}$ is smooth on $\mathbb{R}^n$ (ie, smooth as a mapping $\mathbb{R}^n \to \mathbb{R}^{n+1}$).

Let $\sigma(x) = (x_1,...,x_n,-x_{n+1})$ (just reverses the last coordinate). Note that $\sigma$ is a diffeomorphism between $\mathbb{R}^{n+1}$ and $\mathbb{R}^{n+1}$, $\sigma(U_N) = U_S$ and $\sigma = \sigma^{-1}$. Then it is easy to see that $\phi_S = \phi_N \circ \sigma$. Furthermore, $\phi_S^{-1} = \sigma \circ \phi_N^{-1}$. The smoothness properties of $\phi_S$ and $\phi_S^{-1}$ are the same as those of $\phi_N$, $\phi_N^{-1}$ with appropriate changes (ie, replace $N$ by $S$).

It follows that $\phi_N \circ \phi_S^{-1}$ is smooth (as a mapping $\mathbb{R}^n\setminus \{0\} \to \mathbb{R}^n$, noting that $\phi_S^{-1}(0) = N$).

share|improve this answer
    
thank you very much! –  Kyle Schlitt Oct 28 '12 at 6:14
    
You are very welcome! –  copper.hat Oct 28 '12 at 6:20

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.